The changing energy landscape in the Gulf strategic implications - Bahgat, Gawdat (Gulf Research Center book series, 2015)
Extreme fluctuations in oil prices (such as the dramatic fall from mid-2014 into 2015) raise important strategic questions for both importers and exporters. In this volume, specialists from the US, the Middle East, Europe and Asia examine the rapidly evolving dynamic in the energy landscape, including renewable and nuclear power, challenges to producers including the shale revolution, and legal issues._x000B_Each chapter provides in-depth analysis and clear policy recommendations.